Preparation of Smart Surfaces Based on PNaSS@PEDOT Microspheres: Testing of E. coli Detection - Tomšík, Elena; Laishevkina, Svetlana; Svoboda, Jan; Gunar, Kristýna; Hromádková, Jiřina; Shevchenko, Natalia (Sensors (Basel, Switzerland), 2022)
The main task of the research is to acquire fundamental knowledge about the effect of polymer structure on the physicochemical properties of films. A novel meta-material that can be used in manufacturing sensor layers was developed as a model. At the first stage, poly(sodium 4-styrenesulfonate) (PNaSS) cross-linked microspheres are synthesized (which are based on strong polyelectrolytes containing sulfo groups in each monomer unit), and at the second stage, PNaSS@PEDOT microspheres are formed. The poly(3,4-ethylenedioxythiophene) (PEDOT) shell was obtained by the acid-assisted self-polymerization of the monomer; this process is biologically safe and thus suitable for biomedical applications. The suitability of electrochemical impedance spectroscopy for E. coli detection was tested; it was revealed that the attached bacterial wall was destroyed upon application of constant oxidation potential (higher than 0.5 V), which makes the PNaSS@PEDOT microsphere particles promising materials for the development of antifouling coatings. Furthermore, under open-circuit conditions, the walls of E. coli bacteria were not destroyed, which opens up the possibility of employing such meta-materials as sensor films. Scanning electron microscopy, X-ray photoelectron spectroscopy, water contact angle, and wide-angle X-ray diffraction methods were applied in order to characterize the PNaSS@PEDOT films.
Keywords: bicyklické sloučeniny heterocyklické; Polymers; Bridged Bicyclo Compounds, Heterocyclic; microspheres; mikrosféry; PEDOT; impedance; Escherichia coli; polymery; Microspheres; PNaSS; smart surface